2023
DOI: 10.1186/s12978-023-01594-z
|View full text |Cite
|
Sign up to set email alerts
|

Sexual and reproductive health and rights in humanitarian settings: a matter of life and death

Abstract: It is estimated that approximately 4.3 million sexually active persons worldwide will receive poor and/or limited access to Sexual and Reproductive Health (SRH) services in their lifetime. Globally, approximately 200 million women and girls still endure female genital cutting, 33,000 child marriages occur daily, and a myriad of Sexual and Reproductive Health and Rights (SRHR) agenda gaps continue to remain unaddressed. These gaps are particularly pertinent for women and girls in humanitarian settings where SRH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 37 publications
(93 reference statements)
0
3
0
Order By: Relevance
“…This study demonstrated the mixed and negative perceptions toward pregnancy termination services among key community members, which were especially informed by their religious beliefs. The connection between attitudes and religion reflected in other studies conducted in humanitarian settings and others where women are stigmatized due to perceived religious laws [ 48 , 49 ]. Specifically, imams who are highly respected in the Rohingya community considered pregnancy termination as largely unacceptable.…”
Section: Discussionmentioning
confidence: 85%
“…This study demonstrated the mixed and negative perceptions toward pregnancy termination services among key community members, which were especially informed by their religious beliefs. The connection between attitudes and religion reflected in other studies conducted in humanitarian settings and others where women are stigmatized due to perceived religious laws [ 48 , 49 ]. Specifically, imams who are highly respected in the Rohingya community considered pregnancy termination as largely unacceptable.…”
Section: Discussionmentioning
confidence: 85%
“…With a staggering 4.3 million sexually active persons worldwide receiving poor and/or limited access to sexual and reproductive health (SRH) services in their lifetime, 2 one can easily conclude that the percentage of women not receiving appropriate care in war-torn areas such as Gaza is much higher. This editorial therefore addresses concerns regarding sexual and reproductive health of these women.…”
Section: Unheard Voices: Addressing Sexual and Reproductive Health In...mentioning
confidence: 99%
“…Numerous studies and reports have examined the impact of the COVID-19 pandemic on access to and utilization of RMCAH services, including emergency obstetric and new-born care, finding widespread disruptions in Africa [ 5 , 6 , 11 ]. Many health facilities faced challenges including diversion of resources to the COVID-19 response compromising the provision of regular services, leading to reduced access to and utilization of essential care [ 5 , 11 , 12 ]. Several studies reported a decline in antenatal and postnatal care utilization during the pandemic with fear of infection, transportation difficulties, and restrictions on movement being among the major contributors to this decline [ 11 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%